A alimentação escolar no contexto da pandemia de covid-19 em uma comunidade quilombola - DIAS, Liliane de Nazaré Melo (2023)
Introduction: the covid-19 pandemic impacted the way school feeding was run in quilombola communities. Objective: to describe the distribution and composition of school feeding kits in the pandemic period in a quilombola community in the state of pará. methodology: cross-sectional, descriptive study with 26 families living in a quilombola community, located in the municipality of moju-pa, from november to december/2021. Results: twenty-six quilombola families participated in the study, which were assisted with 04 distributions of kits in the period studied. regarding the composition of the kits, according to the classification of the food guide for the brazilian population, there was a predominance of fresh or minimally processed foods (64%), but did not contemplate the community's eating habits. but they did not contemplate the community's eating habits. regarding the sociodemodegramrate characteristics of the interviewed families, 84.6% reported 1 to 5 people living in the house, with a predominance of men (52%), higher frequency in the age groups of 1 to 10 years (28.9%) and 11 to 20 years (26.4%) and complete elementary education (52.9%). regarding monthly family income, 77% of families received less than one minimum wage and 84.6% were beneficiaries of an income transfer program. Conclusion: Quilombola families have a prevalence of male people, with low schooling and low income. The kits distributed were predominantly composed of fresh and minimally processed foods, with no fruit and vegetables, and did not respect the eating habits of families.